2019
DOI: 10.1111/jicd.12433
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinicopathological characteristics and direct immunofluorescence studies in oral lichenoid lesion in Thai patients

Abstract: Aim To investigate the correlation between the clinicopathological characteristics, serum antinuclear antibody (ANA) and direct immunofluorescence (DIF) findings in oral lichen planus (OLP) and oral lichenoid lesion (OLL). Methods Fifty three Thai patients with red and white lesions were divided into 3 groups: 17 cases of OLP, 19 cases of OLL and 17 cases of oral lichenoid drug reaction (OLDR), respectively. The medical records, photographs, histopathological evaluation and laboratory ANA and DIF results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
(45 reference statements)
1
8
1
Order By: Relevance
“…OLLs secondary to autoimmune bullous diseases possess characteristic findings on DIF, namely intercellular mucosal and linear BMZ deposition of immunoreactants corresponding to the diagnosis of pemphigus and pemphigoid, respectively [43]. Nevertheless, more oftentimes, the DIF features cannot invariably differentiate between different causes of OLLs [17, 44-46]. Apart from the diagnosis of autoimmune bullous disorders, our study confirms no difference in the pattern or primary site of immunoglobulin/complement deposit among the three groups.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…OLLs secondary to autoimmune bullous diseases possess characteristic findings on DIF, namely intercellular mucosal and linear BMZ deposition of immunoreactants corresponding to the diagnosis of pemphigus and pemphigoid, respectively [43]. Nevertheless, more oftentimes, the DIF features cannot invariably differentiate between different causes of OLLs [17, 44-46]. Apart from the diagnosis of autoimmune bullous disorders, our study confirms no difference in the pattern or primary site of immunoglobulin/complement deposit among the three groups.…”
Section: Discussionsupporting
confidence: 51%
“…Direct immunofluorescence (DIF) findings are frequently positive in both conditions. OLE most commonly demonstrates granular deposition of multiple immunoreactants on the basement membrane zone (BMZ), whereas OLP reveals the presence of fibrinogen along the mucosal-submucosal junction (MSJ) [17, 18]. However, in many circumstances, the diagnosis remains difficult as overlapping lupus erythematosus/lichen planus, nonspecific, and/or negative features are frequent DIF findings for both conditions [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, despite the questionable relationship between chronic in ammation and carcinogenesis, recent studies suggest that it could promote genetic and epigenetic changes that might lead to the development of oral SCC. [30][31][32] The presence of epithelial dysplasia is reported in the literature in 0.5-25% of OLP cases 12,21,33,34 and 5.6-27.2% of LLO cases. 21,33 Concerning the degree of epithelial dysplasia, Vijayan and Muthukrishnan 35 in 2022 found that out of 250 OLP lesions, 14 (5.6%) exhibited epithelial dysplasia, with 12 having mild epithelial dysplasia and 2 moderate.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Irani et al 34 observed that among 112 OLP lesions, 12 (10.7%) showed epithelial dysplasia, with ve cases having mild epithelial dysplasia and seven having moderate. 35 Finally, in 2019, Tikkhanarak et al 33 found epithelial dysplasias in 5.6% of a sample of 36 LLO cases (one LLO with mild epithelial dysplasia and one LLO with mild to moderate epithelial dysplasia).…”
Section: Discussionmentioning
confidence: 99%